Radiographic localization of supernumerary teeth: a narrative review - Sreekanth Kumar Mallineni; Robert Prashanth Anthonappa; Jayakumar Jayaraman; Nigel Martyn King (Frontiers in Dental Medicine)
ObjectivesTo conduct a narrative review of the published literature on the localization techniques to identify the best technique for the localization of supernumerary teeth.MethodsAn extensive search of literature published in English between January 1966 and May 2024 was conducted using the “Medline via PubMed” and “Cochrane database” databases. The keywords included in the search were “localization” “radiographs”, and “impacted teeth”, or “un-erupted teeth”, or “supernumerary teeth” or “supernumerary tooth”. The citation lists from the included articles were examined to identify additional reports and a hand search was also conducted. Kappa statistics were used for intra-examiner reliability.ResultsThe initial search yielded 4,864 citations, subsequently examined and supplemented by a hand search to find additional studies. Commonly used techniques for the localization of supernumerary teeth are the horizontal tube shift technique, vertical tube shift technique, vertex occlusal technique, and cone-beam computerized tomography.ConclusionThe most commonly used localization techniques for supernumerary teeth are horizontal tube shift, vertex occlusal, vertical tube shift, and cone-beam computerized tomography. Conventional radiographs only provide two-dimensional views of 3-dimensional structures. Three-dimensional imaging alone can provide accurate data on impacted supernumerary teeth but, the need for this film has to be justified because of the higher radiation exposure.